1996
DOI: 10.1128/jb.178.14.4099-4104.1996
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-coupled energy transduction in the newly isolated thermoalkaliphilic strain LBS3

Abstract: Strain LBS3 is a novel anaerobic thermoalkaliphilic bacterium that grows optimally at pH 9.5 and 50؇C. Since a high concentration of Na ؉ ions is required for growth, we have analyzed the primary bioenergetic mechanism of energy transduction in this organism. For this purpose, a method was devised for the isolation of right-side-out membrane vesicles that are functional for the energy-dependent uptake of solutes. A strict requirement for Na ؉ was observed for the uptake of several amino acids, and in the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 31 publications
5
22
0
Order By: Relevance
“…The function of this ion in neutrophiles (Lolkema et al, 1994), as well as alkaliphiles (Krulwich & Guffanti, 1989 ;Krulwich et al, 1990) and some extremophiles (Speelmans et al, 1995), is either as a coupling ion for energy transduction or in pH homeostasis. We have demonstrated previously that Na + ions play a crucial role in the energy transduction of strain LBS3 T (Prowe et al, 1996). This was also supported by the fact that Na + could not be replaced by K + in the growth medium.…”
Section: Salt Tolerancesupporting
confidence: 53%
See 3 more Smart Citations
“…The function of this ion in neutrophiles (Lolkema et al, 1994), as well as alkaliphiles (Krulwich & Guffanti, 1989 ;Krulwich et al, 1990) and some extremophiles (Speelmans et al, 1995), is either as a coupling ion for energy transduction or in pH homeostasis. We have demonstrated previously that Na + ions play a crucial role in the energy transduction of strain LBS3 T (Prowe et al, 1996). This was also supported by the fact that Na + could not be replaced by K + in the growth medium.…”
Section: Salt Tolerancesupporting
confidence: 53%
“…3c). As reported previously, Na + ions play a major role in the energy transduction of this micro-organism ; K + ions have no such effect (Prowe et al, 1996). Based on these results, it can be concluded that A. gottschalkii LBS3 T depends strictly on Na + ions for growth.…”
Section: Salt Tolerancesupporting
confidence: 53%
See 2 more Smart Citations
“…20,21) L-Ami-no acids are transported into these bacterial cells via proton-or sodium-dependent amino acid transport systems. The uptake of amino acids by the extremely acidophilic, thermophilic archaeon Picrophilus oshimae 22) has been reported.…”
Section: )mentioning
confidence: 99%